The Novel Coronavirus Infection of COVID-19 in HIV Positive Patients and Predictors of an Unfavorable Outcome in In-Patient Settings - N. D. Urushadze; N. Yu. Pshenichnaya; L. E. Parolina; I. A. Lizinfeld; I. A. Vasilyeva (Туберкулез и болезни лёгких)
The objective: to identify speciﬁc features of the COVID-19 course in HIV positive patients and risk factors for unfavourable outcomes in such patients.Subjects and Methods. Patients with COVID-19 regardless of their HIV status admitted to hospital were enrolled in a retrospective observational study.Results. HIV positive patients experienced a more severe course of COVID-19 including more extensive lung tissue damage and severe respiratory failure. Shortness of breath was more common of patients with HIV infection. Laboratory tests revealed adecreased antiviral immune response, signs of anemia and liver damage, and a tendency to develop blood clots. When developing a prognostic logistic regression model in patients with COVID-19 and HIV infection, it was revealed that the risk of an unfavorable outcome was associated with such factors as a decrease in the relative number of lymphocytes and level of total protein in peripheral blood at the moment of admission to hospital.Conclusions. Given the elevated risk of a severe course and unfavorable outcome of COVID-19 in case of concurrent HIV infection, it is necessary to monitor symptoms of respiratory failure in these patients, and if they appear, make a decision about hospitalization at an earlier stage of the disease.